Respuesta :
Step-by-step explanation:
Our expression;
[tex](9w^2+7w-2)+(8w^2-8w-7)-(-5w^2+5w+4)[/tex]
Also represented as after using the distributive property;
[tex]9w^2+7w-2+8w^2-8w-7+5w^2-5w-4[/tex]
Simplify;
[tex]9w^2+7w-2+8w^2-8w-7+5w^2-5w-4[/tex]
[tex]22w^2+7w-2-8w-7-5w-4[/tex]
[tex]22w^2-6w-2-7-4[/tex]
[tex]22w^2-6w-13[/tex]
Answer:
22w² - 6w - 13
Step-by-step explanation:
Given expression: (9w² + 7w - 2) + (8w² - 8w - 7) - (-5w² + 5w + 4)
Step-1: Open the parenthesis
- ⇒ (9w² + 7w - 2) + (8w² - 8w - 7) - (-5w² + 5w + 4)
- ⇒ 9w² + 7w - 2 + 8w² - 8w - 7 + 5w² - 5w - 4
Step-2: Combine like terms
- ⇒ 9w² + 7w - 2 + 8w² - 8w - 7 + 5w² - 5w - 4
- ⇒ w²(9 + 8 + 5) + w(7 - 8 - 5) + (-2 - 7 - 4)
Step-3: Simplify the expression
- ⇒ w²(9 + 8 + 5) + w(7 - 8 - 5) + (-2 - 7 - 4)
- ⇒ w²(22) + w(-6) + (-13)
- ⇒ 22w² - 6w - 13
Therefore, the simplified expression is 22w² - 6w - 13.